(untitled) (Research, Society and Development, 2020)
The exploitation of low content ores became possible due to the technological development. The tailing production from the mineral processing increased, leading the need of the number and capacity increase of the dams. As consequence, dam failure became more frequent, exemplified by Brumadinho/MG and Mariana/MG events in years 2019 and 2015. This article has the objective of applying the multivariate statistical cluster technique named k means to identifying the tailing dams registered in Brazilian Register of Dams of the National Mining Agency that presents similar characteristics to the failed dams from the last years. The technique was successfully applied and it was identified six cluster of dams. The failed dams were located in groups 1 and 2. Besides, the Brazilian tailing dams with high emergency level were located in the same cluster of failed dams and presents similar characteristics. This information does not attest that the dams from cluster 1 and 2 are unstable, but they must to be carefully evaluated.